2020
DOI: 10.2147/dddt.s269236
|View full text |Cite
|
Sign up to set email alerts
|

<p>Downregulation of miR-200a Protects Mouse Leydig Cells Against Triptolide by Triggering Autophagy</p>

Abstract: Background MicroRNAs play important roles in testicular development and spermatogenesis. Previous research has indicated that the level of miR-200a was significantly upregulated in patients with different spermatogenic impairments. However, the mechanism by which miR-200a regulated spermatogenic impairments remains unclear. Methods Leydig cells were treated with triptolide (TP) to mimic spermatogenic impairments. CCK-8 and flow cytometry were used to detect the prolifer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 33 publications
(33 reference statements)
0
7
0
Order By: Relevance
“…In addition, triptolide increased miR-26a expression in rat Leydig cells, which decreased GSk 3β mRNA levels and inhibited testosterone production ( Liang et al, 2019 ). Another study also reported that triptolide induced Leydig cell apoptosis, and this effect might be highly associated with miR-200 ( Miao et al, 2020 ). These results suggested that miRNAs might play an important role in triptolide-induced Leydig cell apoptosis.…”
Section: Discussionmentioning
confidence: 87%
“…In addition, triptolide increased miR-26a expression in rat Leydig cells, which decreased GSk 3β mRNA levels and inhibited testosterone production ( Liang et al, 2019 ). Another study also reported that triptolide induced Leydig cell apoptosis, and this effect might be highly associated with miR-200 ( Miao et al, 2020 ). These results suggested that miRNAs might play an important role in triptolide-induced Leydig cell apoptosis.…”
Section: Discussionmentioning
confidence: 87%
“…For example, the microRNA miR-200a is upregulated in patients with spermatogenesis disorders. ATG7 was identified as a direct binding target of this microRNA [ 61 ]. Interestingly, triptolide (TP), a diterpenoid triepoxide, can increase the expression of miR-200a in the MLTC-1 Leydig cell line and suppress autophagy in these cells.…”
Section: Autophagy and The Regulation Of Male Reproductive Cellsmentioning
confidence: 99%
“…Triptolide (TP) is the primary active compound in the Traditional Chinese Medicine (TCM) herb Tripterygium wilfordii Hook F. (TWHF), which possesses a diverse range of immunosuppressive and anti-inflammatory properties . Multiple studies have shown that triptolide is an autophagy modulator and its activity is associated with the up-or down-regulation autophagy (Chan et al 2017, Li et al 2017b, Miao et al 2020, Xie et al 2019. Because of its neuroprotective effects, the therapeutic potential of triptolide for AD has attracted significant attention (Li & Hao 2019).…”
Section: Triptolide Regulates Autophagy Induced By Aβ 1-42mentioning
confidence: 99%